Konsep Dai dalam Buku Anggukan Ritmis Kaki Pak Kyai Karya Emha Ainun Nadjib - Agus Budiono (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2021)
DaÃ is a key aspect in the success of da'wah. Wrong in the meaning of the role and implementation, the purpose of da'wah will also be difficult to achieve. This is the focus of a Muslim scholar and humanist Emha Ainun Nadjib (Cak Nun) through his work entitled â€œAnggukan Ritmis Kaki Pak Kyaiâ€. Using this type of qualitative research with hermeneutic approach, this study tries to find out how the ideality of the daÃ concept is contained in the book â€œAnggukan Ritmis Kaki Pak Kyaiâ€ by Emha Ainun Nadjib. The results of this study found that according to Emha is what he described in writing in the context of Kyai Sudrun's character composition. His figure is humanist and able to break the paradigm of people's thinking which often judges a daÃ only in terms of mere formality. Therefore, Emha embody the more substantive character of Kyai Sudrun and tried to fight the formal narrative about daÃ which at that time was considered the most â€œarabicâ€ representation of the real daÃ. On the other hand, Emha daÃ had to show their locality without reducing the Islamic substance that had to be conveyed.